Dietary sorbitol and mannitol: food content and distinct absorption patterns between healthy individuals and patients with irritable bowel syndrome. (3rd August 2013) - Yao, C. K.; Tan, H.‐L.; van Langenberg, D. R.; Barrett, J. S.; Rose, R.; Liels, K.; Gibson, P. R.; Muir, J. G.
Abstract: Background: Sorbitol and mannitol are naturally‐occurring polyol isomers. Although poor absorption and induction of gastrointestinal symptoms by sorbitol are known, the properties of mannitol are poorly described. We aimed to expand data on food composition of these polyols, and to compare their absorptive capacities and symptom induction in patients with irritable bowel syndrome (IBS) and healthy individuals. Methods: Food samples were analysed for sorbitol and mannitol content. The degree of absorption measured by breath hydrogen production and gastrointestinal symptoms (visual analogue scales) was evaluated in a randomised, double‐blinded, placebo‐controlled study in 21 healthy and 20 IBS subjects after challenges with 10 g of sorbitol, mannitol or glucose. Results: Certain fruits and sugar‐free gum contained sorbitol, whereas mannitol content was higher in certain vegetables. Similar proportions of patients with IBS (40%) and healthy subjects (33%) completely absorbed sorbitol, although more so with IBS absorbed mannitol (80% versus 43%; P  = 0.02). Breath hydrogen production was similar in both groups after lactulose but was reduced in patients with IBS after both polyols. No difference in mean (SEM) hydrogen production was found in healthy controls after sorbitol [area‐under‐the‐curve: 2766 (591) ppm 4 h –1 ] or mannitol [2062 (468) ppm 4 h –1 ] but, in patients with IBS, this was greater after sorbitol [1136 (204) ppm 4 h –1 ] than mannitol [404 (154) ppm 4 h –1 ; P  = 0.002]. Overall gastrointestinal symptoms increased significantly after both polyols in patients with IBS only, although they were independent of malabsorption of either of the polyols. Conclusions: Increased and discordant absorption of mannitol and sorbitol occurs in patients with IBS compared to that in healthy controls. Polyols induced gastrointestinal symptoms in patients with IBS independently of their absorptive patterns, suggesting that the dietary restriction of polyols may be efficacious.